2009
DOI: 10.1002/app.30141
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of one epoxy system bearing fluorene moieties

Abstract: Diglycidyl ether of bisphenol fluorene (DGEBF) and 9,9-bis(4-aminophenyl) fluorene (BPF) were synthesized to introduce more aromatic structures into an epoxy system, and their chemical structures were characterized with Fourier transform infrared spectroscopy, NMR, and mass spectrometric analysis. The dynamic curing behavior of the DGEBF/BPF system was investigated with differential scanning calorimetry. DGEBF was cured with BPF, diaminodiphenylsulfone (DDS), and diaminodiphenylmethane (DDM), and E-44 (bisphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“… Literature values of rubbery modulus data collected using SC . An assumed misplaced decimal point results in shifting the circled points the data to the left.…”
Section: Discussionmentioning
confidence: 99%
“… Literature values of rubbery modulus data collected using SC . An assumed misplaced decimal point results in shifting the circled points the data to the left.…”
Section: Discussionmentioning
confidence: 99%
“…The M1 /DGEBA/DDS blends had better thermal stability than M1 /DGEBA/DDM blends because the sulfuryl group in DDS had better thermal resistance properties than the methylene in DDM. That thermosets using DDS as curing agents had better thermal stability than thermosets based on the same monomer using DDM as curing agents could be found in some investigation by other authors 38. Anyway, thermosets based on M1 are one kind of LCETs with excellent thermal stabilities.…”
Section: Resultsmentioning
confidence: 72%
“…This indicated that DHPOP had a higher reactivity than DGEBA when cured with DDM. On one hand, the flexible ether linkage embedded in DHPOP maybe weaken steric hindrance in the curing process . On the other hand, this phenomenon may be also attributed to the electronic effect of oxygen atom, which increase the reactivity of epoxy groups and decrease the activation energy of curing reaction.…”
Section: Resultsmentioning
confidence: 99%